Hospital-at-Home Patient Fall Predictors - Cristian Madrid, MD; Karthik Gnanapandithan, MD; Michael G. Heckman, MS; Sophia G. Blumenfeld, BS; Rachel Gothot, MHA; Colt Cowdell, MD; Michael J. Maniaci, MD; Sally Anne Brown, JD; Jennifer B. Cowart, MD; Margaret Paulson, DO; Wendelyn Bosch, MD (Mayo Clinic Proceedings: Innovations, Quality & Outcomes)
Objective: To evaluate predictors of falls in the hospital-at-home (HaH) setting from a single institution in 3 US states. Patients and Methods: In this retrospective study of HaH patients residing in Florida, Wisconsin, and Arizona, we identified 51 patients who fell and were matched to 153 patients without fall, between July 2020 and July 2023. Patient demographics and clinical characteristics were collected, including age, sex, race, Charlson Comorbidity Index, geographic location, body mass index, Hester Davis Scale, admission diagnosis, continuous intravenous infusion, polypharmacy, marital status/life partnership, area deprivation index, and use of supplemental oxygen. Association of patient characteristics were examined using unadjusted and multivariable logistic regression models (July 29, 2020 to July 5, 2023). Results: The rate of falls was 6.8 per 1,000 patient bed-days. In multivariable analysis, we found that older age (odds ratio [OR; per each 10-year increase], 1.37; P=.043), higher Charlson Comorbidity Index (OR [per each 5-unit increase], 1.80; P=.012), and supplemental oxygen use (OR, 2.05; P=.045) were independent predictors of falls in the HaH setting. Although not statistically significant, an increased risk of falls was observed in patients with a diagnosis of respiratory disorder (OR, 2.07; P=.075). Conclusion: In patients hospitalized at home, the risk of falls may increase with older age, higher Charlson Comorbidity Index, and supplemental oxygen use. Mitigation strategies to prevent falls in patients with these risk factors should be considered in the HaH setting.